Kontribusi Daerah Aceh terhadap Perkembangan Awal Hukum Islam di Indonesia. - Kamaruzzaman BA (Al-Jami'ah Research Centre, 1999)
This paper tries to trace the contribution of Aceh in the development of Islamic law in lndonesia. so far the study on the early development of Islamic law is rarely carried out. The condition might be influenced by scholars' statement that the school of thought that spread widely in Aceh was shafi'1ryah. The statement seems to be agreed since no study tries to trace the contribution of Aceh in the development of Islamic law in lndonesia. In this paper, the writer try to prove that Shafi,iyyah was not the only school spread in Aceh, but there was shi'ite Islamic law in Aceh. After a deep study, begun with the description of Islamic law, then followed by the arrival of Islam in Aceh, the writer comes to a conclusion that shi'i school come to Aceh before shafi’i. Shafi’i school came and developed after the demolishment of shi'i. This opinion is supported by the traditions of Aceh that still go on. This is also supported by the lineage of perlak sultans. Meanwhile, the writer is involved in the polemic on the existence of shi'ite in Indonesia. The polemic was raised by Azyumardi Azra with his statement that there was no shi'it's influence in Aceh, let alone in Nusantara during 9th century. Azra's opinion could be caused by his fear of local historiography. He said that local historiography is difficult to encounter other sources and historical development. In this paper, the writer encounters Azra's opinion using the book